The effect of repeated post-weld heat treatment on low-carbon steel ASTM A216WCB. (December 2015) - D'Arcy, Cathal; Ruddy, Mark; Haines, John; Gibbons, John P; Stanton, Kenneth T
The subject of this study is the effect of repeated post-weld heat treatment on valves made of low-carbon steel, ASTM A216WCB. Post-weld heat treatment is a common technique used to alleviate detrimental stresses induced in the vicinity of the weld as a result or the weld process. This investigation was set out to characterise the effect of such heat treatments in the bulk material away from the weld site if carried out as part of a regular industrial maintenance routine. By exposing the steel to varying numbers of heat treatments up to a maximum of 20 cycles and performing tensile testing, hardness tests and metallographic analysis, it was possible to quantitatively assess the mechanical properties of the material. The objective was to determine whether the material's properties were altered beyond the requirements of the applicable standard for the alloy. A 3.7 ℃/min ramp rate and a hold temperature of 615 ℃ ± 15 ℃ were used for each heat treatment cycle. The study found that A216WCB's hardness decreased by 6%, to 141 Hv after 20 heat treatment cycles. Tensile tests showed that there was a decrease in yield strength of 2.98%, to 300.6, while ultimate tensile strength fell by 6.9% to 483.3 MPa after 20 cycles. The ultimate tensile strength values were approaching those listed in the material standard for A216WCB, whereas yield strength values were well within the minimum specified by the standard.